Management of large mandibular ameloblastoma - a case report and literature reviews - Abdullah, Kahairi; Raja Lope Ahmad, Raja Ahmad Al'konee; Leman, Wan Ishlah; Harun, Norra (Universiti Sains Malaysia, 2008)
Ameloblastoma is a slow growing benign tumour of the jaw and patients usually present late after the tumour achieved considerable size to cause facial disfigurement. Diagnosis mainly from tissue biopsy and characteristic findings on plain X-rays does assist in differentiating between types of ameloblastoma. The challenges in the management of this tumour are to provide complete excision as recurrence may occur in incomplete removal and also to reconstruct the bony defect in order to give reasonable cosmetic and functional outcome to the patient.